2015
DOI: 10.1158/1940-6207.capr-14-0181-t
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Metformin on Mammary Carcinogenesis in Nondiabetic Rat and Mouse Models

Abstract: Epidemiologic studies have shown that diabetics receiving the biguanide metformin, as compared to sulfonylureas or insulin, have a lower incidence of breast cancer. Metformin increases levels of activated AMPK and decreases circulating IGF-1; encouraging its potential use in both cancer prevention and therapeutic settings. In anticipation of clinical trials in non-diabetic women, the efficacy of metformin in non-diabetic rat and mouse mammary cancer models was evaluated. Metformin was administered by gavage or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 40 publications
2
34
1
Order By: Relevance
“…In contrast to our findings, a limited number of rodent studies have suggested that metformin does not affect mammary carcinogenesis (10,11). However, there are key differences in study design between our study and these previous reports that include variations in rodent age at initiation with MNU, diet, and dosage of metformin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, a limited number of rodent studies have suggested that metformin does not affect mammary carcinogenesis (10,11). However, there are key differences in study design between our study and these previous reports that include variations in rodent age at initiation with MNU, diet, and dosage of metformin.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of preclinical studies of mammary carcinogenesis and in vitro studies using breast cancer cell lines are consistent with this assertion of metformin's beneficial effects (4-9). Even so, other preclinical studies of mammary carcinogenic models failed to see any effect of metformin when the animals were fed a low fat diet and exhibited no metabolic dysfunction (10,11). These conflicting reports suggest that there may be specific factors and metabolic conditions that confer a tumor's sensitivity to metformin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of effect for metformin in non-diabetic preclinical rodent models of breast cancer has been recently reported (37). These findings are confirmed and extended in this work by evaluation of additional biguanides.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies showed an increase in female animal life span independent of effect on tumor incidence 31, 33 , although in a study by Anisimov et al, the 4.4% increase in mean life span in females was counterbalanced by a 13.4% decrease in male animal mean life spans 34 . A recent study using both an ER-positive rat carcinogenesis model and Neu+/p53 knockout mice showed no effect of metformin administered at doses achievable in human beings 36 . Of note, the tumor burden and proliferation index trended toward increases with metformin treatment, the latter reaching statistical significance.…”
Section: Animal Carcinogenesis Studiesmentioning
confidence: 97%